Development and testing of candidate items for inclusion in a new rheumatoid arthritis stiffness patient-reported outcome measure. (11th April 2017) - Halls, Serena; Dures, Emma; Kirwan, John R; Pollock, Jon; Baker, Gill; Edmunds, Avis; Hewlett, Sarah
Abstract: Objective: To qualitatively develop and test a set of candidate items for a new RA stiffness patient-reported outcome measure (PROM) that capture the patient perspective. This is an essential first step in PROM development, prior to quantitative development, assessment and validation. Methods: Focus groups further examined the previously developed stiffness conceptual model and explored the patient perspective regarding stiffness assessment. Data were analysed using thematic analysis. An iterative process of item development was then performed by the expert study team of researchers, patients and clinicians, based on the two qualitative datasets and informed by measurement theory and guidelines. Finally, these candidate items were tested using formal cognitive interview methodology and subsequently refined. Results: Sixteen RA patients from the UK participated in focus groups. Data confirmed the conceptual model of the RA patient experience of stiffness and provided insight into stiffness assessment, including suggestions regarding patient-relevant stiffness assessment categories such as impact, location and timing. These data informed the development of 77 candidate stiffness PROM items, including multiple formats for some. Eleven RA patients participated in cognitive interviews. Minor changes were made to items to enhance understanding and 32 items were removed, resulting in 45 candidate PROM items. Conclusion: Rigorous qualitative methodology and considerable patient involvement has underpinned items for a new RA stiffness PROM with strong content validity. Crucially, patient involvement broadened assessment beyond early morning stiffness duration, which may address existing PROM limitations. Items are now suitable for quantitative item reduction, structural development of the final PROM and validation.